1992
DOI: 10.1182/blood.v80.10.2503.2503
|View full text |Cite
|
Sign up to set email alerts
|

Roles of erythropoietin, insulin-like growth factor 1, and unidentified serum factors in promoting maturation of purified murine erythroid colony-forming units

Abstract: We have used 75% to 90% pure murine erythroid colony-forming units (CFU- E) to delineate the processes and factors underlying their maturation. These CFU-E form 32 cell colonies and are drawn from what we term generation I of a six-generation long maturation sequence (Landschulz et al, Blood 79:2749, 1992). Applying assays of 59Fe-heme biosynthesis and colony numbers as measures of maturation and analyses of DNA degradation as an index of programmed cell death, we find that (1) erythropoietin (Epo) enhances ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 29 publications
1
21
0
1
Order By: Relevance
“…There also might be a functional relationship between members of the cytokine receptor superfamily as Bazan (1990) suggested. Together with stem cell factor, Epo controls the proliferation of erythroid progenitors (Boyer et al, 1992). Similar positive effects of IGF-I on erythropoiesis were demonstrated in vivo in animal studies (Kurtz et al, 1990;Tsarfaty et al, 1994).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…There also might be a functional relationship between members of the cytokine receptor superfamily as Bazan (1990) suggested. Together with stem cell factor, Epo controls the proliferation of erythroid progenitors (Boyer et al, 1992). Similar positive effects of IGF-I on erythropoiesis were demonstrated in vivo in animal studies (Kurtz et al, 1990;Tsarfaty et al, 1994).…”
Section: Discussionmentioning
confidence: 65%
“…In several reports it has been demonstrated that insulin-like growth factor-I (IGF-I) has stimulatory actions on granulopoiesis in animals (Fu et al, 1991;Wiedermann et al, 1991;Arkins et al, 1993) and erythropoiesis in vitro and in vivo (Kurtz et al, 1988;Merchav et al, 1988;Kurtz et al, 1990;Correa & Axelrad, 1991;Dainiak et al, 1991;Boyer et al, 1992;Merchav et al, 1992;Muta & Krantz, 1993;Sanders et al, 1993;Bechensteen et al, 1994;Muta et al, 1994;Tsarfaty et al, 1994). Administration of human recombinant growth hormone (rhGH) is known to increase serum IGF-I concentration (Salomon et al, 1989;Binnerts et al, 1992b;Moller et al, 1993).…”
mentioning
confidence: 99%
“…Their ndings indicate that IGF has an Epo-like activity, providing strong evidence for the existence of an Epo-independent pathway for normal human adult erythropoiesis, possibly operative when Epo levels are low. Boyer et al (49) found that the relative effect of IGF-I was strongest in the absence of Epo, con rming the observation that the IGF-I effect was less evident when Epo levels were high. IGF-I receptors have been found on reticulocytes from rats and on erythrocytes from humans (50).…”
Section: Growth and Its Effect On Erythropoiesismentioning
confidence: 86%
“…EPO has been shown as the principal factor that controls proliferation, differentiation, and apoptosis of human erythroid progenitor cells through its special cell surface receptor (EPOR) signaling. Several cytokines such as SCF, IL-3, GM-CSF, IGF-1, and hepatocyte growth factor (HGF) were reported to enhance the proliferation and/or maturation of erythroid progenitors in vitro, but failed to do so without EPO, suggesting the central role of EPO in erythropoiesis (21)(22)(23)(24)(25)(26)(27)(28). No factor so far has been reported to possess activity similar to that of EPO, especially on relatively late stage erythroid progenitors.…”
Section: Discussionmentioning
confidence: 99%